SEX RATIO OF FRESHWATER CATFISH NOTOPTERUS NOTOPTERUS (HAMILTON). FROMBHIMA RIVER, MAHARASHTRA - SHENDGE, A.N.; MANE, U.H. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Sex ratio of a freshwater catfish. Notopterus notopterus (Hamilton) from Bhima river near Bhigwan, Pune District, Maharashtra has been studied. The overall sex ratio males to females were 1.18:1.0. Males outnumbered females, although the sex ratio showed no significant deviation in the population. Males outnumbered females before spawning (May - June). During peak spawning (August - September) females outnumbered males. Males outnumbered females from 210-259 mm, whereas females outnumbered males from 260- 289 mm. In larger length groups 290- 329 mm Only females were recorded. Males were not recorded above 289mm length.